Water Sensitive Coatings Deposited by Aerosol Assisted Atmospheric Plasma Process: Tailoring the Hydrolysis Rate by the Precursor Chemistry. Issue 11 (15th May 2015) - Mertz, Grégory; Fouquet, Thierry; Ahrach, Hicham Ibn El; Becker, Claude; Phan, Trang N. T.; Ziarelli, Fabio; Gigmes, Didier; Ruch, David
Abstract : Biocompatible plasma polymers are expected to be used in various applications in medicine such as drug delivery with a controlled release. In this context we investigated the possibility to monitor the kinetic of hydrolytic degradation of plasma polymers by tailoring the chemistry of the precursor. A homemade precursor way synthesized by grafting acrylate function on both side of a polycaprolactone diol (PCL diol) to produce a PCL diacrylate characterized by IR, NMR, and MS to confirm its chemical structure. Acrylates constitute a promising class of precursors to improve the retention of the integrity of the precursor by working in soft plasma conditions. The plasma polymerization of the so‐synthesized precursor have been highlighted by means of a multi technique analytical strategy and ensured the retention of hydrolyzable ester function of the precursor. Finally the thickness consumption during immersion in PBS were performed and found to be slower as compared to the degradation kinetic of a plasma polymerized methacrylic anhydride. Abstract : A homemade precursor was synthesized by grafting acrylate function on both side of polycaprolactone diol (PCL diol) to produce PCL diacrylate. Then the precursor was hence fed between the plasma dis‐charge in soft plasma condition to obtain a thin insoluble coating with a higher reten‐tion of the precursor chemistry as duly shown by a multi technique characterization step. The hydrolytic degradation mimicking the conditions of the human body were also performed.